1995
DOI: 10.1037/1040-3590.7.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Positive Automatic Thoughts Questionnaire.

Abstract: The Positive Automatic Thoughts Questionnaire (ATQ-P) was designed to assess the frequency of positive self-statements. This article reports original data and reviews other studies that have used the ATQ-P. These data show that the reliability and the norms of the ATQ-P appear stable and that the ATQ-P is inversely associated with negative affective states but unrelated to conditions such as medical condition not accompanied by psychological distress. The ATQ-P also shows adequate convergent and discriminate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
1
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 60 publications
7
65
1
4
Order By: Relevance
“…Regarding the cognitive content, a number of endorsement measures of self-talk provide valence-based scores, that is, scores focused on the positive versus negative nature of inner speech (e.g., Burnett, 1996;Ingram, Kendall, Siegle, Guarino, & McLaughlin, 1995). Questionnaires based exclusively on the valence pose the problem that, under the headings of negative and positive thoughts, cognitions of a very different nature are assessed.…”
mentioning
confidence: 99%
“…Regarding the cognitive content, a number of endorsement measures of self-talk provide valence-based scores, that is, scores focused on the positive versus negative nature of inner speech (e.g., Burnett, 1996;Ingram, Kendall, Siegle, Guarino, & McLaughlin, 1995). Questionnaires based exclusively on the valence pose the problem that, under the headings of negative and positive thoughts, cognitions of a very different nature are assessed.…”
mentioning
confidence: 99%
“…Several authors have placed increasing emphasis on the role of cognition in the origin, maintenance, and treatment of different types of psychopathology [2,3]. Haaga, Dyck, and Ernst [4] pointed out that this theoretical position focused on the automatic negative cognitions encountered in psychological disorders, whilst others [1,5] postulated that a specific relationship between positive and negative cognition might be a key determinant in psychopathology. Kendall suggested that examination of both negative and positive cognitions could contribute to a better understanding of the health-pathology relationship [5].…”
Section: Introductionmentioning
confidence: 99%
“…Automatic thoughts are explored in several theories dealing with psychopathology [1]. Several authors have placed increasing emphasis on the role of cognition in the origin, maintenance, and treatment of different types of psychopathology [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Successful integrative and instrumental reminiscence may contribute to the accumulation of mental resources that are related to depression and anxiety. Three such resources that are known to be related to mental health are meaning in life , mastery , and positive thoughts (Ingram, Kendall, Siegle, Guarino & McLaughlin, 1995).…”
Section: Life-review Interventionsmentioning
confidence: 99%
“…Successful integrative and instrumental reminiscence may contribute to the accumulation of mental resources that are related to depression and anxiety. We will focus here on three such resources that are known to be related to mental health: meaning in life , mastery , and positive thoughts (Ingram, Kendall, Siegle, Guarino & McLaughlin, 1995). Successful integrative reminiscence may contribute to a sense of meaning in life as it contributes to fi nding coherence and purpose in one's own life experiences.…”
Section: Introductionmentioning
confidence: 99%